Indian food and welfare schemes: Scope for digitization towards cash transfers - Shweta Saini; Sameedh Sharma; Ashok Gulati; Siraj Hussain; Joachim von Braun (University of Bonn, Center for Development Research (ZEF), 2017)
The Indian Government has identified a unique opportunity in using Information and Communication Technology (ICT) based solutions to streamline its inefficient, ineffective, and expensive subsidy operations. By bringing all subsidies, mainly food and fertilizer subsidy, under the ICT platform, the government aims to make its subsidy operations and delivery mechanisms- transparent, efficient, and effective. Food subsidy is the largest component of government's subsidy bill and is focus of the paper. Authors evaluate the possibility of substituting the existing system of subsidized grain distribution, i.e. Public Distribution System (PDS) with ICT-based Direct Benefit Transfer (DBT) system. Implementing DBT for food will imply substitution of the existing physical grain entitlement system under PDS/NFSA with a cash transfer made directly into the bank accounts of the beneficiaries. The ongoing policy discussions and strategies for executing DBT-food in India are observed to be prescriptive in nature and suffer, inter alia, on two accounts. One, they view the transition of states from existing PDS to ICT based DBT food as one-disruptive change rather than as an incremental process that contributes to making a system gradually ready for the big transition. Two, by prescribing a uniform timeline for implementation in all the 36 Indian states and Union Territories (UTs), policy makers fail to acknowledge the diverse economic, social, and financial vulnerabilities in different parts of country. The paper attempts to address this gap in political thinking and strategy formulation and present a case for a phased approach to roll out DBT in the Indian food sector. It proposes a scientific way of evaluating a state/UT's 'readiness' for shifting from PDS to DBT in food. The 'readiness' analysis involves studying a state's performance on three parameters: their demographics, performance of existing PDS and the current state of their banking infrastructure. Identification of these parameters draws on learning from national and international experiences in DBT for food, in particular that of Chandigarh and Puducherry (where it is completely rolled-out) that are detailed in the paper's first part. The analysis reveals that in the next five years i.e. by 2022, all Indian states and UTs can replace their existing PDS with DBT-food. We divide the 36 states/UTs into four Phases. The states that are most ready for DBT transition (Phase 1) are Punjab, Goa, Delhi, Daman and Diu, Chandigarh and Puducherry and they may make this shift in the next one year i.e. by 2018. In the second phase are six states- Haryana, Tamil Nadu, Andhra Pradesh, Telangana, Karnataka and Kerala- who may transition to DBT by 2019. States with a very high share of nation's poor and malnourished and/or have high banking infrastructural deficits, are put into the Phase 3 and these 11 states are Madhya Pradesh, Chhattisgarh, Rajasthan, Jharkhand, Bihar, Odisha, Uttar Pradesh, West Bengal, Dadra & Nagar Haveli, Maharashtra and Gujarat. These states may take about three and half years (i.e. by 2021) for implementing DBT-food. The last phase comprises of 13 states (Arunachal Pradesh, Assam, HP, J&K, Manipur, Meghalaya, Mizoram, Nagaland, Sikkim, Tripura, Uttarakhand, A&N Islands and Lakshwadeep) that have been given a special category status by Union Government and the erstwhile Planning Commission. These 13 states have a low population density, or are geographically located in remote areas, and/or are socio-politically and economically sensitive areas. The states in Phase 3, 4, and 5 are given more time before they implement DBT-food so that they address their existing infrastructural deficits. For these states, the paper proposes an interim phase consisting of a reformed PDS employing IT solution for identity verification of beneficiaries. For cities, towns, urbanised areas in states in the last three Phases whose performance on the three parameters is better than their respective states, the paper proposes a hybrid approach whereby they can shift more quickly to DBT even as the rest of the State puts in place the PDS reform package. Overall, a phased approach with PDS reforms, maximum digitization and use of ICT and JanDhan-Aadhaar-Mobile (JAM) technologies and a secure criteria-based preparation for a shift to DBT in food is proposed in the paper. In order to make the transition from PDS to DBT-food successful, specific policy recommendations are made in the paper. Some of these recommendations are: 1. Open market grain availability: This will make or break the transition. Unless the Centre and the states ensure availability of enough food grains in the open market, the transition to DBT food is unlikely to be successful; 2. Inclusive financial integration: Even if we have adequate availability of food grains in the open market, if the banking infrastructure is not inclusive, DBT food will not deliver. Thus, simultaneous efforts are required to increase the number of bank branches, ATMs and BCs. There is a need to include Post offices, cooperative banks and even large PACS (which currently are not part of the core banking system) into this system; 3. Innovations in payment channels: Apart from vertical expansion of the banking network, we also recommend horizontal expansion of payment channels; 4. Hedge farmers' market risks: As a consequence of DBT food when the MSP procurement operations are scaled-down, the Centre and states should together work towards creating and facilitating deep and wide alternative markets for farmers to sell their surplus food grains; a. Provision of an unconditional cash transfer to the farmer: The government may also consider, in the longer run, substituting the existing input subsidy support for agriculture (including fertiliser subsidy) and output price support to farmers with a cash transfer made directly into the farmers' bank accounts; 5. Introduction of policies to complement the system: In order to avoid diversion of the transferred cash towards vices, government should ensure that the entire economic system grows up to meet the increased demand that is likely to result from greater disposable incomes with a household. In particular, there is a need to ensure commensurate increase and stable supply of high-value food, education and healthcare services; 6. Adequacy of the food subsidy amount: If instead of MSP in the food subsidy formula (1.25*MSP - CIP), we can have the Economic cost, then the current problem of 'inadequacy' of the food subsidy transfer amount, faced in Chandigarh and Puducherry, may be resolved; and 7. Leadership and political will: Political motivation in the States to implement the DBT or reforms in the PDS is a vital factor determining the future of PDS reforms. Overall, DBT has the potential to make way for a system of social security or universal basic income, a special income support- provided to every citizen- whose size can be adjusted to his or her needs and vulnerability. Although the concept of basic income is still at its infancy even in the most developed countries, the path to creating such a system has to be through the DBT. Notwithstanding initial problems in implementation and the problems of labour markets that DBT may trigger, a cash transfer systems has become a potent tool in the government's armoury of social welfare. As the country transitions from its low income position to becoming the world's fastest growing economy in a few years, a cash transfer system delivering a social security transfer to all can promote a growth process that is inclusive, efficient and sustainable.
Keywords: Q18; Q01; I38; E64; D61; H53; 330; National Food Security Act (NFSA); FCI; Cash Transfers; CCTs; Financial Inclusion; direct benefit transfer (DBT); Public Distribution System (PDS); Indian agriculture; Aadhaar; JAM; Grain Leakages